2017
DOI: 10.1111/jpn.12635
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an in vitro system to simulate equine foregut digestion and the influence of acidity on protein and fructan degradation in the horse′s stomach

Abstract: SummaryThe aim of this study was to improve an in vitro system in order to gather optimized information on the digestion of different forages in the horse 0 s upper gastrointestinal tract. Therefore, foregut digestion of several forages was simulated in vitro (Part 1). The effect of different pH values on in vitro fructan degradation of two selected grasses (Part 2) was tested subsequently. Part 1: We hypothesized that our system produces representative results simulating digestive processes in the upper alime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…This finding is in accordance with other studies that also described the fermentation of inulin and/or grass fructans starting in the lower gut [20, 40]. The degradation might possibly be started by acid hydrolysis in the stomach [23, 24]. Furthermore, the WSC content in the large intestine was zero in the current study, indicating a largely complete degradation in the foregut.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in accordance with other studies that also described the fermentation of inulin and/or grass fructans starting in the lower gut [20, 40]. The degradation might possibly be started by acid hydrolysis in the stomach [23, 24]. Furthermore, the WSC content in the large intestine was zero in the current study, indicating a largely complete degradation in the foregut.…”
Section: Discussionsupporting
confidence: 93%
“…Hitherto, some authors speculated from in vivo or ex vivo results that the fermentation of inulin-type fructans, as well as inulin itself, begins in the foregut [20, 21] and particularly the stomach [21], which might cause negative effects concerning stomach health. In vitro studies support the suggestion that the digestion of fructans in particular (in terms of acid hydrolysis) might not occur in the large intestine alone (as previously assumed) [22, 23, 24]. Consequently, we hypothesized that i) the feeding of FOS + inulin as active prebiotic ingredients originating from Jerusalem artichoke meal has an impact on the microbiota of the entire GIT and that ii) prebiotic compounds act as possible substrates for the microbiota in the stomach.…”
Section: Introductionsupporting
confidence: 78%
“…(), Ince et al. () and Strauch et al (), fructans are prone to be already decomposed in the lower gut, including the stomach where the DP might be of particular importance (Strauch et al, ). Glatter et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, PP exhalation of methane and hydrogen in equines indicated that inulin started to be fermented already in the foregut (Coenen et al., ). In vitro studies with grass fructans suggested that under specific conditions, acid hydrolysis in the stomach leads to the decomposition of grass fructans (Ince et al., ; Strauch et al, ). When fructose is released and not immediately fermented by gut microbes, it might be absorbed in the equine digestive tract by specific transporters (Glut 5), which are highly abundant in the small intestine (Fernandez‐Castaño Merediz et al., ; Taylor et al, ), and is transported through the bloodstream into the liver.…”
Section: Discussionmentioning
confidence: 99%
“…All the ingredients used for the experimental diets were treated with digestive enzymes using the in vitro method with the technique described by Strauch et al [ 28 ]. Briefly, each sample was performed in triplicates.…”
Section: Methodsmentioning
confidence: 99%